REPRESENTATION OF POPULAR CULTURE IN THE ELECTRONIC CINEMA (REFREED TO AS SINETRON) SITTI NURBAYA SHOWN BY THE TVRI AND THE TRANS TV - I Nyoman Suaka (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2024)
The Sitti Nurbaya research on the TV-series’ form is due to under consideration that, thisshow is to be very fond of Indonesian society. The TVRI and Trans TV-version of SittiNurbaya`s TV-series happened to provoke a polemic in mass media. The director and theproducer of this series obtained compliments and scorn, even just in order to bechallenged by a group of audience. Another audience threatened in order to stop the SittiNurbaya series show because it is considered to be able to bring down the Minangkabaupeople’s prestige. The problem of the research is how the Sitti Nurbaya`s novel and TVseriesaudiovisual text structure are? flow does the critics’ perspective watch the TVRIand Trans TV-version of Sitti Nurbaya`s series? What kind of ideology does support theshow of TVRI and Trans TV-version of Sitti Nurbaya`s series?The theory which is used in this research is popular culture, ideology, inter-text andperception theories. This kind of studies model refers to the opinion which stated that thecultural is always political and popular culture becomes a hegemony and ideology.The destructive sign system transposition such as, distortion and deconstruction, in largeof number can be found in Sitti Nurbaya`s TV-series’ Trans TV show. This text destructioncovers plot, background, character and also the extrinsic aspects. The form which isevaluated as the appreciative part is, the story is returned to its context.The television media capitalism strength adapted - Sitti Nurbaya`s novel as literature text- into TV-series form through text transposition i.e. crossing, destructing, erasing,humiliating, and protesting reference text politically. That thing as postmodern culturalphenomenon because the cultural studies creators evaluate modem cultural has failed,because gives high cultural more attention and neglects low cultural which is identical withthe popular culture. The difference on that show version can not let go of from thehegemony or media power. TVRI station is the only station in Indonesia, belongs to thegovernment while Trans TV belongs to the private. Keywords: representation, cultural popular, novel, electronica sinema